Universal amplitude ratios in the three-dimensional Ising model - Caselle, M.; Hasenbusch, Martin (Journal of physics. A, Mathematical and general, 1997)
We present a high precision Monte Carlo study of various universal amplitude ratios of the three-dimensional Ising spin model. Using state of the art simulation techniques we study the model close to criticality in both phases. Great care is taken to control systematic errors due to finite size effects and correction to scaling terms. We obtain , and . Our results are compatible with those obtained by field theoretic methods applied to the theory and high- and low-temperature series expansions of the Ising model. The mismatch with a previous Monte Carlo study by Ruge et al remains to be understood.
Gesehen am 08.07.2022